Permeable Pavement with Escoria (Revista de Diavulgación L'esprit Ingénieux, 2024)
Pervious concrete is a mixture of water, cement and coarse aggregate of a single size and generates a porous structural material. It is an alternative for the coating of roads, trails, parking, gardens, among other spaces and has as one of its results which improves the control of rainwater. To innovate in the topic of ecological paving, in the present investigation it was inquired about the optimal dosages of the aggregates of the concrete, with the use of coarse and fine aggregate coming from the blast furnace slag of the Acerías Paz de Rio. The process was investigated to design a porous concrete and the characterization of the material was made, especially the gravel and the one coming from the blast furnace slag. Three mixtures were designed for concrete cylinders with different percentages of aggregates, especially coarse ones. For the first test, two samples with 50/50 and 70/30 percentages of coarse aggregate and slag were used, for the second, 45% of coarse slag 45% of gravel and 10% of fine slag were used, for the third test it was used 45% coarse slag, 45% gravel and 10% fine slag, but with different amounts of water. From the cylinders, the percentage of absorption, percentage of voids, porosity, the flow through the cylinders of samples 2 and 3 and the strength of the concrete were determined.
Keywords: Permeable concrete; Drainage; Rigid pavement; Porosity; Project